Public awareness of the constitutional monarchy among society in Kota Kinabalu, Sabah / Omar Sarif Omal Lamin, Syahirah Suhaime and Nurfaizah Abbdullah - Omal Lamin, Omar Sarif; Suhaime, Syahirah; Abbdullah, Nurfaizah (Universiti Teknologi MARA, Sabah, 2023)
This study focuses on the issue of public awareness of constitutional monarchy in Kota Kinabalu, Sabah. Public awareness of the constitutional monarchy is essential to ensure that society understands the significance of actions taken by the constitutional monarchy in Malaysia. In conducting this study, researchers used univariate analysis, covering two main variables: the roles of the Yang Di-Pertuan Agong (YDPA) and the roles of the Conference of Rulers. These variables are from the Federal Constitution. The study was conducted through an online questionnaire that involved 60 respondents, who were divided into two groups: 30 Bumiputera respondents and 30 non-Bumiputera respondents. The data were collected and analysed using descriptive statistics through the Statistical Package for the Social Sciences (SPSS).